THE IMPACT OF DIFFERENT CONVERTER KIT TYPES ON THE PERFORMANCE OF A DIESEL ENGINE UTILIZING BIOSOLAR AND LPG FUEL - Rosyadi, Imron; Caturwati, Ni Ketut; Satria, Dhimas; Suprayogi, Dedy Triawan; Ula, Shofiatul; Relawan, I G Putu (Trends in Mechanical Engineering Research, 2023)
The impact of the converter kit type on the performance of diesel engines using biodiesel and LPG fuel has been explored. Converter kits play a vital role in transforming the fuel supply system, and experiments have been conducted to assess their influence on various engine performance parameters. The findings of the study indicate that the selection of a converter kit significantly affects the performance of dual-fuel diesel engines (biodiesel and LPG). Gas Heater converter kits, including type 1, type 2, and type 3 variations, were scrutinized in this research. Testing revealed variations in LPG-Biodiesel fuel mixing ratios depending on the type of converter kit employed. For instance, Gas Heater type 3 achieves the highest value with a mixing ratio of 14.4. Furthermore, the performance of the engine in terms of power and torque is also impacted by the type of converter kit utilized. Gas Heater type 1 exhibits peak performance, with power reaching 5.4 kW and torque measuring 34.81 Nm. Despite the operational costs of dual-fuel diesel engines tending to be higher than those using pure biodiesel, the research concludes that the choice of the converter kit type can have a substantial effect on engine performance, particularly regarding fuel efficiency.